Distinguer entre savoir critique et opinion critique : quelle posture de neutralité pour l'enseignant en EMC ? - Gaid Andro
All of the CNESCO (National Council for the Evaluation of the School System) reports and teacher surveys on the pedagogical implementation of moral and civic education (EMC) in the classroom establish the same observation: there is a notable discrepancy between the political and civic investment in this subject expressed by the institution and the reality perceived by teachers and pupils regarding the learning actually carried out. This article aims to shed light on this discrepancy by identifying the implicit tensions at work among teachers confronted with the civic and didactic challenges of CME. Our hypothesis is that the embarrassment of teachers, and a fortiori of beginning teachers, lies in the difficulty of distinguishing, on the one hand, the professional neutrality necessary for a civic education that assumes its critical perspective, and, on the other hand, and as a corollary, of identifying the knowledge really at stake in a teaching detached from the scientific disciplinary framework. Based on the observation of a group of students of master 1 MEEF in situation of preparation of lessons, our work tries to circumscribe the professional framework of the teaching neutrality in EMC by operating a distinction between the critical knowledge and the critical opinion in the various times of implementation in the class.